Amorphous Tin‐Based Composite Oxide: A High‐Rate and Ultralong‐Life Sodium‐Ion‐Storage Material. Issue 8 (27th November 2017) - Yang, Xu; Zhang, Rong‐Yu; Zhao, Jing; Wei, Zhi‐Xuan; Wang, Dong‐Xue; Bie, Xiao‐Fei; Gao, Yu; Wang, Jia; Du, Fei; Chen, Gang
Abstract: Energy‐storage technology is moving beyond lithium batteries to sodium as a result of its high abundance and low cost. However, this sensible transition requires the discovery of high‐rate and long‐lifespan anode materials, which remains a significant challenge. Here, the facile synthesis of an amorphous Sn2 P2 O7 /reduced graphene oxide nanocomposite and its sodium storage performance between 0.01 and 3.0 V are reported for the first time. This hybrid electrode delivers a high specific capacity of 480 mA h g −1 at a current density of 50 mA g −1 and superior rate performance of 250 and 165 mA h g −1 at 2 and 10 A g −1, respectively. Strikingly, this anode can sustain 15 000 cycles while retaining over 70% of the initial capacity. Quantitative kinetic analysis reveals that the sodium storage is governed by pseudocapacitance, particularly at high current rates. A full cell with sodium super ionic conductor (NASICON)‐structured Na3 V2 (PO4 )2 F3 and Na3 V2 (PO4 )3 as cathodes exhibits a high energy density of over 140 W h kg −1 and a power density of nearly 9000 W kg −1 as well as stability over 1000 cycles. This exceptional performance suggests that the present system is a promising power source for promoting the substantial use of low‐cost energy storage systems. Abstract : The illustration of amorphous tin‐based composite oxide (ATCO) as a high‐performance anode for a sodium ion battery is shown with a high rate of performance of 180 mA h g −1 at current of 2 A g −1 for 15 000 cycles. Quantitative kinetic analysis reveals that the sodium storage is governed by pseudocapacitance, particularly at high current rates.